(untitled) (Collection of scientific works «Modern structures of metal and wood», 2021)
Experimental data on strength, deflections and cracking in beams are presented. Beams are made with dimensions 2000x200x100mm with steel and basalt-plastic (BFRP) reinforcement. They have been tested for static and low-cycle reloading. The results of studies of the main parameters of the performance of research elements are presented in the form of the corresponding experimental-statistical dependences for the actions of operational and destructive loads with the same design factors. With the help of stochastic and graphical analysis, the influence of the type of reinforcement and design factors on the strength and deformation characteristics, as well as on the crack resistance of experimental samples - beams, is estimated.